Systemic lupus erythematosus complicated with liver cirrhosis in a patient with Papillon-Lefèvre syndrome. (December 2014) - Yasudo, H; Ando, T; Takeuchi, M; Nakano, H; Itonaga, T; Takehara, H; Isojima, T; Miura, K; Harita, Y; Takita, J; Oka, A
We report the first case of a girl who presented with Papillon-Lefèvre syndrome (PLS) and subsequently developed systemic lupus erythematosus and liver cirrhosis. This indicates that autoimmune diseases can be a complication in patients with PLS. Cathepsin C gene mutations were not found in our patient or her mother. Thus, other genetic factors may have been involved in this patient.